2022
DOI: 10.32604/biocell.2022.014997
|View full text |Cite
|
Sign up to set email alerts
|

The neuroprotection of electro-acupuncture via the PGC-1α/TFAM pathway in transient focal cerebral ischemia rats

Abstract: ATP depletion is one of the pathological bases in cerebral ischemia. Electro-acupuncture (EA) is widely used in clinical practice for ischemia. However, the mechanism of EA remains unclear. The purpose of this study was to investigate whether EA could activate the AMPK/PGC-1α/TFAM signaling pathway and, consequently, increase the preservation of ATP in rats with ischemia. In this study, 48 rats were randomly divided into four groups as a sham-operation control group (sham group), a middle cerebral artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Then, we analyzed the effect of arsenic on the mitochondrial apoptosis pathway and PGC-1α expression in this study; the result showed that there was a negative correlation between apoptosis and PGC-1α, which suggested that PGC-1α plays an important role in arsenic-induced hippocampal neuronal cell apoptosis. Previous studies have shown that brain ATP content is regulated by PGC-1α, and the decrease of PGC-1α reduces the content of ATP [ 46 , 47 , 48 ]. In this study, there was positive correlation between PGC-1α and ATP contents.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we analyzed the effect of arsenic on the mitochondrial apoptosis pathway and PGC-1α expression in this study; the result showed that there was a negative correlation between apoptosis and PGC-1α, which suggested that PGC-1α plays an important role in arsenic-induced hippocampal neuronal cell apoptosis. Previous studies have shown that brain ATP content is regulated by PGC-1α, and the decrease of PGC-1α reduces the content of ATP [ 46 , 47 , 48 ]. In this study, there was positive correlation between PGC-1α and ATP contents.…”
Section: Discussionmentioning
confidence: 99%